The Effect of Warm Compresses of Lemongrass and Moringa Leaves on Reducing Pain in Arthritis Patients at the Krangkeng Health Center, Indramayu Regency - Putri, Andini Aldila; Sirait, Healthy Seventina; Gunawan, Gugun; Buana, Rozi; Elida, Duma (CV. Strata Persada Academia, 2024)
Rheumatoid Arthritis is an autoimmune disease that causes inflammation of the joints, resulting in pain, stiffness, and swelling. In October 2023, there were 50 cases at the UPTD Krangkeng Health Center, Indramayu. This study aims to determine the effect of warm compresses of boiled lemongrass and moringa leaves on reducing pain in rheumatoid arthritis patients at the UPTD Krangkeng Health Center, Indramayu. This study used a quantitative method with a quasi-experimental design and involved 50 patients using a total sampling technique. Data analysis included univariate analysis, normality test, and bivariate test with Wilcoxon. The results showed that the average pain intensity of the lemongrass group before the intervention was 6.80, and the average after the intervention was 1.20. The average pain intensity of the moringa group before administration was 6.72, and the average after administration was 1.32. The Wilcoxon signed ranks test results were obtained with a p-value of lemongrass = 0.000 and a p-value of moringa = 0.000. This shows a significant decrease in pain after being given a warm compress of boiled lemongrass and a warm compress of boiled moringa leaves. This can be continued as an intervention carried out independently in rheumatoid arthritis patients or by the UPTD Krangkeng Health Center as a non-pharmacological therapy to reduce pain intensity in rheumatoid arthritis patients.